Pathways to philosophy : a multidisciplinary approach - Shrader, Douglas W. (Prentice Hall, 1996)
"Pathways" is an imaginative introduction to the art of philosphical reflection and wonderment. Original essays are combined with classical and contemporary readings from philosophy, science and literature. Both structure and content emphasize the wide-ranging name of the field, its relevance to other disciplines, and the interrelateness of seemingly disparate areas of study.